SISTEM PAKAR PADA TANAMAN APOTEK HIDUP UNTUK PENGOBATAN ALTERNATIF MENGGUNAKAN METODE CERTAINTY FACTOR - Dimas Satriadi; Anton Setiawan Honggowibowo; Yuliani Indrianingsih (Compiler, 2017)
Medical treatment using herbal plants rarely utilized by the society, because most of them didn't know the benefit inside herbal plants. therefore needed an application to educate the society about herbal life. Application system was a product of research by a herbal expert using certainty factor. Certainty factor method was a method that to believe on an event based on expert judment. Besides educating society about the benefit of herbal plants, the expert system could help to provide a consultation. Result of expert system consultation with certainty factor was to minimize uncertainty in medical treatment using herbal plants.